Evaluating the Impact of Radiologic Procedures on Nursing Care Planning and Patient Recovery Outcomes - Alshammary, Abeer Mohammed; shammry, Awatif Mohammed saud Al; ALshmr, Ahmed Nashmi; Al-Haisi, Aisha Abdo Ahmed; Alnadwi, Budur Zayed; Ali Hawsawi, Ebtehal Mohammed; AlShamerry, Fraih Ayadah Mutlaq; Alshammri, Khaled Farhan; Alwakid, Mohammad Saleh Abdullah; Aldabbous, Mostafa Jamil; et al. (Journal of Posthumanism, 2024)
Background: Radiologic procedures are essential in today’s healthcare system, affecting the whole process from diagnosis through treatment to recovery. The radiologic competency of the hospital, the risk management strategy, and the patient education will all depend on the imaging results. Hence, it is a must to know the radiology-nursing interaction in order to increase safety, improve communication and recovery outcomes. Objective: The review was intended to highlight the current practices, challenges, and opportunities for improvement in clinical and patient-centered outcomes by evaluating the impact of diagnostic as well as interventional radiologic procedures on nursing care planning and patient recovery. Methods: The authors performed a narrative literature review using PubMed and Google Scholar to locate peer-reviewed articles that were published within the time frame of January 2020 to September 2024. The search was done by employing the combination of Medical Subject Headings (MeSH) and free-text keywords related to radiologic procedures, nursing care, and patient recovery. The articles that were chosen for inclusion in the review were the ones that had provided quantitative, qualitative, or mixed-methods research, systematic reviews, and clinical guidelines centered on nursing roles in imaging, interdisciplinary coordination, and recovery outcomes. Results: The data extracted resulted in the identification of five main themes: 1) clinical nursing roles in pre- and post-procedure care, 2) interventional radiology and patient monitoring, 3) communication and education strategies, 4) technological integration, including informatics and imaging analytics, and 5) space barriers of limited training, ethical concerns, and communication gaps. It is a common viewpoint that the coordination of radiologic-nursing practices leads to an increase in the safety, satisfaction, and recovery of patients, but the total implementation across all hospitals is still in progress. Conclusion: Radiologic procedures are vital not only in the nursing care process but also in the recovery outcomes. To maximize the impact of radiology on nursing, comprehensive training, interdisciplinary coordination, and consistent hospital policies across departments are few of the ways